2022
DOI: 10.1080/22221751.2022.2093134
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and genetic characteristics of clinical carbapenem-resistant Acinetobacter baumannii strains collected countrywide from hospital intensive care units (ICUs) in China

Abstract: Acinetobacter baumannii is one of the key Gram-negative pathogens that can cause serious nosocomial infections. In China, a large proportion of clinical A. baumannii strains are multidrug resistant, among which strains resistant to carbapenems are particularly worrisome, as infections caused by such strains may limit the choice of existing antibiotics. We conducted a nationwide and genome-based surveillance on the prevalence and antibiotic susceptibility profile of carbapenem-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Children with low body weight and incomplete immune systems are more susceptible to the invasion of external pathogens and nosocomial infection [ 13 ]. Additionally, limited types of antibiotics are available for children, so cephalosporins, carbapenems, and macrocyclic lipids are widely used, which may lead to drug resistance [ 14 ] The resistance rates of CRKP and CRAB were also found to be higher in the ICU compared with other departments, which is in line with previous research findings [ 2 , 15 , 16 , 17 ]. In developed countries, over 20% of nosocomial infections occur in the ICU [ 18 ], where patients are at a higher risk of MDRO infection due to low organ function; comprised immunity; and underlying diseases such as diabetes, chronic obstructive pulmonary disease, and chemotherapy [ 4 ].…”
Section: Discussionsupporting
confidence: 81%
“…Children with low body weight and incomplete immune systems are more susceptible to the invasion of external pathogens and nosocomial infection [ 13 ]. Additionally, limited types of antibiotics are available for children, so cephalosporins, carbapenems, and macrocyclic lipids are widely used, which may lead to drug resistance [ 14 ] The resistance rates of CRKP and CRAB were also found to be higher in the ICU compared with other departments, which is in line with previous research findings [ 2 , 15 , 16 , 17 ]. In developed countries, over 20% of nosocomial infections occur in the ICU [ 18 ], where patients are at a higher risk of MDRO infection due to low organ function; comprised immunity; and underlying diseases such as diabetes, chronic obstructive pulmonary disease, and chemotherapy [ 4 ].…”
Section: Discussionsupporting
confidence: 81%
“…In China, CRAB strains were prevalent in 71% of the 77 ICUs recruited for nationwide surveillance. Clonal spread of CRAB was found in 38% of the ICUs surveyed, with a total of 22 different clones identified [ 4 ]. During the COVID-19 pandemic, the risk of CRAB co-infection or secondary infection increased among the patients hospitalized with COVID-19 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they also help in adherence to host epithelial cells (Brossard and Campagnari, 2011). The protein is prevalent in A. baumanni strains including clinical and avirulents strains collected from different geographical regions (Liu et al, 2022). A study confirmed the involvement of Bap in modulation of cell surface hydrophobicity(CSH) which further support bacterial adherence to epithelial cells (Brossard and Campagnari, 2011).…”
Section: Role Of Adherence and Motility In Virulencementioning
confidence: 73%